2015
DOI: 10.1371/journal.pone.0127761
|View full text |Cite
|
Sign up to set email alerts
|

The CD14 rs2569190 TT Genotype Is Associated with an Improved 30-Day Survival in Patients with Sepsis: A Prospective Observational Cohort Study

Abstract: According to previous investigations, CD14 is suggested to play a pivotal role in initiating and perpetuating the pro-inflammatory response during sepsis. A functional polymorphism within the CD14 gene, rs2569190, has been shown to impact the pro-inflammatory response upon stimulation with lipopolysaccharide, a central mediator of inflammation in sepsis. In this study, we hypothesized that the strong pro-inflammatory response induced by the TT genotype of CD14 rs2569190 may have a beneficial effect on survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
2
13
0
2
Order By: Relevance
“…Despite frequent findings of poor outcome in patients with CD14 -159 TT genotype, Mansur and coworkers reported improved survival in those patients. 26 Similarly, superior survival in critically ill patients after burn injury was noticed in CD14 -159 TT carriers. 27 In summary, our study indicates the association of CD14 -159 T allele and the presence of extranodal DLBCL and elevated CRP at diagnosis, both previously established as unfavorable clinical parameters.…”
Section: International Journal Of Hematology and Oncologymentioning
confidence: 93%
“…Despite frequent findings of poor outcome in patients with CD14 -159 TT genotype, Mansur and coworkers reported improved survival in those patients. 26 Similarly, superior survival in critically ill patients after burn injury was noticed in CD14 -159 TT carriers. 27 In summary, our study indicates the association of CD14 -159 T allele and the presence of extranodal DLBCL and elevated CRP at diagnosis, both previously established as unfavorable clinical parameters.…”
Section: International Journal Of Hematology and Oncologymentioning
confidence: 93%
“…Similarly pro-and anti-inflammatory cytokines like the interleukin-1 (IL-1) gene family, interleukin-6 (IL-6) and interleukin-10 (IL-10) are associated with different outcomes of septic patients (Fang et al, 1999). Genomic variants of candidate genes involved in pathogen recognition and signal transduction of inflammatory pathways like CD14, Toll-like receptors (TLRs), lipopolysaccharide binding protein (LBP), interleukin-1 receptor-associated kinase (IRAK 4), IRAK 1 may also contribute to the incidence, severity and mortality of infectious complications in the critically ill (Hubacek et al, 2001;Feterowski et al, 2003;Medvedev et al, 2003;Sutherland et al, 2005;Arcaroli et al, 2006;Khor et al, 2007;Chien et al, 2008;Mansur et al, 2015). In addition, it has been recognized that protein cascades involved in the pathophysiology of sepsis, such as the coagulation cascade, represent strong genomic candidate markers for association studies (Hermans et al, 1999).…”
Section: Genomics and Epigenomicsmentioning
confidence: 99%
“…A meta-analysis of 17 studies has shown that carriers of C alleles are exposed to 1.72 odds ratio for septic shock (P=0.03) but this association existed mainly for Asian populations and not for European populations (22). In a recent study of 417 adult patients of western European descent, 30-day survival was 77% among patients with the CT or TT genotype and 87% among patients with the TT genotype (P=0.0261) (23).…”
Section: Prrsmentioning
confidence: 99%